Applications of building information modelling in architecture engineering construction industry [electronic resource] - Ayad Abdullah Mohammed Matafi, 1987-; Abdul Kadir Marsono; Fakulti Kejuruteraan Awam. (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2012